Evaluating biomass and carbon stock responses to thinning and pruning in mature Larix principis-rupprechtii Mayr stands: a case study from Northern China - Ali, Jamshid; Haoran, Wang; Mehmood, Kaleem; Muhammad, Bilal; Hussain, Wakeel; Hussain, Khadim; Shahzad, Fahad; Qun, Yin; Zhongkui, Jia (Frontiers in Forests and Global Change, 2025)
Forestry management practices, such as thinning and pruning, significantly influence biomass accumulation and carbon sequestration, which are critical for climate change mitigation. This study examines the impact of thinning and pruning intensities on biomass and carbon stocks in 50-year-old Larix principis-rupprechtii Mayr plantations at Saihanba Mechanical Forest Farm in Northern China. The research involved 45 plots subjected to 15 treatments, each with 3 replicates. The Comprehensive assessments were made for aboveground biomass (AGB), belowground biomass (BGB), and total biomass. The statistical significance of differences between treatment groups was assessed using Analysis of Variance (ANOVA) and Regression analysis. The results demonstrated significant reductions in AGB, BGB, and total biomass with increased thinning intensity, up to 42.9% for AGB and 42.6% for BGB compared to the control treatment. The percentage decrease in total biomass from the control treatment, T0P0, to the most intensive treatment, T4P2, is approximately 42.5%. The percentage decrease in total carbon over the control treatments is about 42.7%. The soil organic carbon (SOC) decreased by 35.6% compared to the control treatment. Pruning influences tree structure and health. The findings highlight the complex interactions between forest management practices and carbon dynamics, emphasizing the adoption of light to moderate thinning and pruning strategies. These approaches can sustain the forest's carbon sequestration capabilities while maintaining forest health and productivity. This study provides empirical evidence to guide future forest management decisions, emphasizing the critical balance needed to maximize forest health and carbon sequestration potential.